Dealing with dragons - Wrede, Patricia C., 1953- (San Diego : Magic Carpet Books/Harcourt, 2002)
Bored with traditional palace life, a princess goes off to live with a group of dragons and soon becomes involved with fighting against some disreputable wizards who want to steal the dragons' kingdom.
"First published 1990"--T.p.verso.
7.3
Young Adult
Young Adult
Wilson's Children
Wilson's Junior High School
Keywords: Princesses -- Fiction; Dragons -- Fiction; Wizards -- Fiction; Fantasy; Princesses -- Fiction; Dragons -- Fiction; Wizards -- Fiction; Fantasy fiction